Mekanisme Koping Family Caregiver Merawat Lansia Yang Mengalami Proses Penuaan - Ninda Ayu Prabasari; Linda Juwita; Steven Aldo Marcello (Universitas Malahayati Lampung, 2025)
ABSTRACT The aging process will occur in the elderly, wheresoever will be some body impairment. The role of family caregivers is important to accompany and help the elderly, while caring for the elderly, family caregivers will use coping mechanisms as a form of reaction or defense effort in dealing with stressors which in this case are stressors when caring for the elderly. Researchers want to know the description of the family caregiver’s coping mechanisms while caring for the elderly at home. Non-experimental research using a cross-sectional approach with a descriptive research type, the population of family caregivers living with the elderly was 76 people who corresponding the inclusion and exclusion criteria. The majority of family caregivers used positive coping mechanism strategies (planful, self-controlling, seeking-social, accepting, and positive reappraisal) and sometimes or rarely used negative coping mechanism strategies (confronting, distancing, and escape avoidance). Coping mechanisms can occur due to several factors that support these efforts to overcome problems or stressors faced by family caregivers in caring for the elderly. Keywords: Coping Mechanism, Family Caregiver, Elderly ABSTRAK Proses penuaan akan terjadi pada lansia, dimana penurunan fungsi tubuh akan terjadi. Peran family caregiver penting untuk mendampingi dan membantu lansia, selama merawat lansia family caregiver akan menggunakan mekanisme koping sebagai bentuk reaksi atau upaya pertahan dalam menghadapi stresor yang dalam hal ini adalah stresor ketika merawat lansia. Peneliti ingin mengetahui gambaran dari mekanisme koping family caregiver selama merawat lansia dirumah. Penelitian non-eksperimental menggunakan pendekatan cross-sectional dengan jenis penelitian deskriptif, populasi family caregiver yang tinggal bersama lansia sebanyak 76 orang yang memenuhi kriteria inklusi dan eksklusi.Mayoritas family caregiver menggunakan strategi mekanisme koping yang positif (planful, self-controlling, seeking-social, accepting, dan positive reappraisal) dan kadang atau jarang menggunakan strategi mekanisme koping yang negatif (confronting, distancing, dan escape avoidance). Mekanisme koping dapat terjadi akibat beberapa faktor yang mendukung usaha tersebut untuk mengatasi masalah atau stresor yang dihadapi oleh family caregiver dalam merawat lansia. Kata Kunci: Mekanisme Koping, Family Caregiver, Lansia